(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Nanosized material SnO2 was obtained by a sol-gel technique to create a sensor purposed for determination of carbon monoxide concentration in air. Platinum was added to the nanosized tin dioxide by a wet impregnation method using H2PtCl6 solution. According to TEM data the average size of the SnO2 particles in the obtained nanosized tin dioxide was equal to 10–11 nm. Sensor nanomaterials based on SnO2 and Pt/SnO2 powders which were sintered at 620°C in air consisted of spheric particles with average sizes 20 and 14–15 nm, correspondingly. Phase compositions of the obtained nanomaterials were studied by the XRD method. Only a phase of cassiterite was detected for the nanomaterials with and without platinum. The absence of any reflexes of platinum-containing phases in the diffraction pattern of Pt/SnO2 is most likely due to the low content of platinum in the material. It was shown that dopping the nanosized SnO2 materials by platinum lead to increase their catalytic activities in the reaction of CO oxidation: the temperature of practically complete conversion of CO at Pt/SnO2 catalyst was equal to 110 °С. The sensor created on the base of Pt/SnO2 nanomaterial was found to be more sensitive to CO than the one created without platinum in the range of its heater power consumption 0.25–0.45 W. High catalytic activity of the Pt/SnO2 nanomaterial in the reaction of CO oxidation is a reason of such sensor sensitivity increase. The dependence of the sensitivity of the sensor on the heater power consumption has a maximum that can be explained by the change of the amount of oxygen chemisorbed on the sensor gas sensitive layer when the sensor temperature is increased. The maximal sensor sensitivity to CO is g = 10 at the optimal heater power consumption of the sensor (0.3 W). The created sensor to CO based on the nanomaterial Pt/SnO2 was found to be very fast. The response time of the sensor (τ0,9) was equal to 4,5 s and the relax time (τrelax) was equal to 9.8 s. It was shown that the created sensor based on nanomaterial Pt/SnO2 has high sensitivity to carbon monoxide and possess good dynamic properties, which makes the sensor to be promising for usage it in gas analytical devices purposed for determination of CO in air.